Digital Spaces, Analogue Thinking: Some Thoughts on Screendance - Zanotti, Marisa (The International Journal of Screendance, 2019)
With the rapid development of camera technologies and screening platforms over the past 10 years comes an expanded screendance field that opens itself up to new screen bodies, sites, and audiences. Are there new considerations and indeed less-positive effects in this potential? This writing reflects on process, production, and duration—now and in the past—in screendance, performance, and artists’ films, to address the question, ‘where are we now?’